Literacy of Employee Salary Distribution Through M-Banking Muamalat Din in Al-Rifa'ie - Nurwakhidah, Ana; Soleh, Amir (Sahwahita: Community Engagement Journal, 2024)
Mobile banking has become an inseparable part of modern society's life. This service allows bank customers to carry out various financial transactions online just by using a smartphone. This convenience and practicality is the main attraction for users, encouraging a shift from conventional transactions at banks to digital. Realizing the potential and benefits of mobile banking, Unira Malang students were moved to organize community service activities in the form of fieldwork programs (PKL). This activity focuses on assistance and literacy about MuamalatDIN, a mobile banking service from Bank Muamalat, one of the leading Sharia banks in Indonesia.